Accelerating Economic Transformation through Strengthening Halal Food Downstream Competitiveness for National Resilience - Euis Amalia; Muhammad Hanafi (Jurnal Lemhannas RI, 2025)
Purpose: This study explores the integration between food downstreaming and the halal industry through value chain integration theory, industry competitiveness concept and astagatra national resilience perspective. Study Design/Methodology/Approach: The research was conducted using a qualitative descriptive method. Data were collected through systematic literature analysis and interviews with various experts in the fields of economics and wealth sources. The descriptive-analytical analysis was conducted using the framework or concepts of Porter's diamond model, CRT, SWOT (EFAS and IFAS), and TOWS. Findings: The Porter's Diamond Model analysis indicates that the halal food downstreaming industry in Indonesia is not yet fully competitive, with the CRT analysis identifying four root causes. Then, based on the SWOT analysis, the coordinates (2.43; 2.78) were obtained, indicating the need for a "turnaround" strategy to enhance competitiveness and address the identified weaknesses in the halal food downstreaming industry. Originality/Value: This study present national strategy to enhance halal food downstreaming based on the value chain integration theory. Indonesia needs to expand market penetration through trade diplomacy, product diversification, culinary-based branding, and credible halal certification. The government needs to develop industrial clusters, provide incentives for supporting industries, partner with research institutions and universities, and adopt international standards. Furthermore, capacity building and awareness among MSMEs need to be strengthened through national-scale training programs that focus on best practices, technological advancements, and market access strategies. Finally, cross-sector policy integration needs to be improved.